2008
DOI: 10.1038/sc.2008.158
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous vasoconstriction as a measure of incipient autonomic dysreflexia during penile vibratory stimulation in spinal cord injury

Abstract: Study design: Measurement of haemodynamic responses, cutaneous blood flow and sweat release during penile vibratory stimulation (PVS) in spinal cord-injured men. Objective: To assess the validity of using markers of sympathetic activity (cutaneous blood flow and sweat release) as a measure of incipient autonomic dysreflexia during PVS in spinal cord-injured men. Setting: Prince of Wales Medical Research Institute, Australia. Subjects: Ten spinal cord-injured men with injuries ranging from C3 to T6. Methods: Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
4
7
0
Order By: Relevance
“…Likewise, the studies also describe a wide variety of HR responses, ranging from a reduction of 17.5 bpm in HR below baseline during AD 84 to an increase of 13 bpm above baseline. 78 As noted earlier, individuals with an injury at or above T6 are more likely to experience more severe episodes of AD; this finding is consistent with the literature investigating the cardiovascular response to sexual activity in individuals living with SCI. 33,78,81 The variability in reported peak SBP in the literature has given rise to disagreement regarding how severe the SBP increases during PVS can be.…”
Section: Cardiovascular Responses During Pvs Proceduressupporting
confidence: 88%
See 2 more Smart Citations
“…Likewise, the studies also describe a wide variety of HR responses, ranging from a reduction of 17.5 bpm in HR below baseline during AD 84 to an increase of 13 bpm above baseline. 78 As noted earlier, individuals with an injury at or above T6 are more likely to experience more severe episodes of AD; this finding is consistent with the literature investigating the cardiovascular response to sexual activity in individuals living with SCI. 33,78,81 The variability in reported peak SBP in the literature has given rise to disagreement regarding how severe the SBP increases during PVS can be.…”
Section: Cardiovascular Responses During Pvs Proceduressupporting
confidence: 88%
“…The mechanisms underlying of 156 mm Hg in individuals with cervical SCI. In contrast, other studies 76,78,79 that record BP continuously report a noticeably higher average peak SBP during PVS ranging from an increase of 10 mm Hg up to 107 mm Hg above baseline. The only major difference between these experimental studies was the method of BP monitoring.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In the absence of central modulation, reflexly evoked vasoconstriction elicited by distension of visceral organs, or by some other unheeded afferent input from caudal to the lesion, is exaggerated (21). In SCI patients, spinal reflex-evoked vasoconstriction is most readily studied in the skin (e.g., 7,8,34), where modified neural control of blood flow results in poor thermoregulation (21) and may contribute to increasing the risk of pressure sores and impair wound healing (11,37).…”
mentioning
confidence: 98%
“…Indeed, we recently showed that weak electrical stimuli applied to the abdominal wall cause pronounced and prolonged cutaneous vasoconstriction and increases in blood pressure, the latter indicating that these stimuli below the lesion level caused coactivation of cutaneous, muscle and splanchnic vasoconstrictor neurones (Brown et al 2007, 2009 a ). Moreover, vibration of the penis in spinal men (a procedure performed to procure semen for fertility assessment) causes a pronounced increase in blood pressure (Sheel et al 2005) and cutaneous vasoconstriction (Brown et al 2009 b ), the latter occurring also in the absence of clinical signs of autonomic dysreflexia (Brown et al 2009 b ).…”
mentioning
confidence: 99%